Microscopic and submicroscopic changes in the hemomicrocirculatory bed of the lungs in the conditions of experimental allergic inflammation - Popko, S. S.; Попко, Світлана Сергіївна (My University, 2022)
Currently, there is a constant increase in the incidence of bronchial asthma in Ukraine, which is motivated by environmental pollution, an increase in the population's allergies, and the deterioration of the nation's gene pool. One of the insufficiently researched phenomena in the study of morphological changes in chronic allergic diseases of the respiratory system is the participation of components of the hemomicrocirculatory bed of the lungs. The above information indicates the relevance of establishing the ultramicroscopic features of the wall of the microvessels of the lungs in the context of the development of an allergic inflammatory process. Our work aimed to determine the microscopic and submicroscopic features of the hemomicrocirculatory bed of the lungs during the experimental allergic inflammatory process. We used 48 male guinea pigs: intact, control, and four experimental groups to achieve the goal. Ovalbumin-induced allergic airway inflammation was simulated for the experimental groups. The study of ultrastructural features was carried out on the study's 23rd, 30th, 36th, and 44th days using the histological method and electron microscopy. It was established that the most significant changes occur during the early period of the development of allergic inflammation in blood capillaries and post-capillary venules. The swelling of the endotheliocytes of the vessels of the hemomicrocirculatory bed led to the formation of microgrowths, resulting in the changed shape of the vascular lumen. At the same time, disorganization and loss of the order of microfilaments, as well as separation of endothelial contacts with the formation of gaps, were determined in endotheliocytes. The signs of dysfunction of the endothelium of the links of the microcirculatory bed and histochemical changes of the surrounding microvessel of the connective tissue in the wall of the respiratory tract and lungs in the animals of the experimental groups are caused by the increased functional activity of perivascular mast cells. Зважаючи на важливу роль гемомікроциркуляторного русла легень для підтримання локального гомеостазу дихальної системи, вивчення його ультрамікроскопічних особливостей при алергічному запальному процесі в легенях є однією з актуальних задач морфології. Мета роботи – визначити основні мікроскопічні та субмікроскопічні зміни гемомікроциркуляторного русла легень в умовах експериментального алергічного запалення. Об’єкт і методи дослідження. За допомогою гістологічного та електронномікроскопічного методів вивчили легені 48 самців морської свинки в умовах експериментального овальбумін-індукованого алергічного запалення. Визначали ультраструктурні зміни компонентів гемомікроциркуляторного русла в умовах експериментального алергічного запалення. Результати. Виявлена закономірність реакції структурних компонентів гемомікроциркуляторного русла у відповідь на сенсибілізацію та інгаляції овальбуміном, що полягає в структурно-функціональній перебудові судин обмінної ланки мікроциркуляторного русла легень сенсибілізованих овальбуміном морських свинок у вигляді повнокрів’я, вазодилатації, збільшення проникності судинної стінки, що призводить до набряку та дезорганізації периваскулярної сполучної тканини. Набряк ендотеліоцитів судин гемомікроциркуляторного русла призводив до формування великої кількості мікровип’ячувань та інвагінацій, внаслідок чого змінювалась форма судинного просвіту. Висновки. Встановлено, що протягом раннього періоду розвитку алергічного запального процесу в легенях спостерігаються ознаки дисфункції ендотелію гемомікроциркуляторного русла та збільшення проникності судинної стінки, підтверджених на ультрамікроскопічному рівні. Виявлені гемомікроциркуляторні зміни зумовлені підвищеною функціональною активністю навколосудиннних мастоцитів, які регулюють перебіг алергічного запального процесу за рахунок впливу на судинну та клітинну реакції.
Мікроскопічні та субмікроскопічні зміни гемомікроциркуляторного русла легень в умовах експериментального алергічного запалення
Popko S. S. - 0000-0002-5533-4556
Keywords: hemomicrocirculatory bed; experimental allergic inflammation; ovalbumin; guinea pig; electron microscopy; гемомікроциркуляторне русло; експериментальне алергічне запалення; овальбумін; морська свинка; електронна мікроскопія